Correlation of morphological patterns of nucleoli in alveolar macrophages with HLA-DR antigen expression in sarcoidosis. Issue 12 (December 1991) - Popp, W; Wachtler, F J
Abstract : BACKGROUND: Alveolar macrophages from patients with sarcoidosis express increased quantities of HLA-DR during activation. Because silver staining has been described as a sensitive indicator of cellular activity a study was performed to examine whether it relates to HLA-DR antigen expression. METHODS: The relation between silver staining patterns of nucleoli and HLA-DR antigen expression was examined in alveolar macrophages collected by bronchoalveolar lavage from 11 patients with pulmonary sarcoidosis and 11 control subjects. RESULTS: The mean (SD) number of silver stained protein dots associated with the nucleolar organiser regions (AgNORs) was significantly higher in alveolar macrophages from patients with sarcoidosis (7.5 (1.5)) than in those from control subjects (5.6 (0.6)). The number of silver stained dots in alveolar macrophages correlated significantly with the intensity and the density of HLA-DR antigen expression in the patients with sarcoidosis. CONCLUSIONS: Silver staining may be a sensitive tool for the investigation of the biological cell activity of alveolar macrophages in sarcoidosis.